Algorithm of management of patient with alcohol-induced liver disease - M. V. Mayevskaya; M. A. Morozova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To present main pathogenic aspects of development of alcohol-induced liver disease (ALD), principles of diagnostics and treatment of this disease.Original positions. The alcohol-induced liver disease includes some variants of parenchymal damage caused by regular alcohol intake: steatosis, alcoholic hepatitis and liver cirrhosis (LC). There are series of factors contributing to ALD development. The main of them include amount of taken alcohol, gender, genetic polymorphism of enzymes involved in alcohol metabolism (метаболизме алкоголя?), nutritional status. At application of alcohol within several days there is a probability of liver steatosis development – the state at which in hepatocytes gather macrovesicular triglyceride inclusions. As a rule, disease has no clinical symptoms, frequently it is a casual diagnostic finding and does not require specific treatment besides abstinence of alcoholic beverages. Alcoholic hepatitis is significantly more severe form of ALD. Manifestation of disease usually appear after another episode of alcohol intake. Severe alcoholic hepatitis, especially if develops on a background of pre-existing LC, in high number of cases is associated to unfavorable life prognosis. Cirrhosis is the end-stage of ALD. Diagnostics of severe ALD forms is based on finding-out past history data indicating alcohol abuse, revealing clinical and laboratory signs of liver failure, ruling out other liver diseases. Therapeutic approach includes complete abstinence from alcohol, wholesome nutrition, application of glucocorticosteroids, anticytokine agents and drugs, containing S-adenosylmethionine. Article presents the clinical case of successful treatment of severe alcohol-induced hepatitis.Conclusion. Pathogenesis of ALD is based on direct toxic operation action of ethanol on one hand and on endotoxemia and increased production of proinflammatory cytokines, on another hand. Based on knowledge of liver damage mechanisms, prognosis of disease and its proper treatment are possible.